Pengaruh Leverage dan Kebijakan Dividen terhadap Volatilitas Harga Saham pada Sektor Properties & Real Estate yang Terdaftar di Bursa Efek Indonesia - Umah, Khirzatul; Kusumawati, Yulia Tri; Anshari, Rahman (Perhimpunan Sarjana Ekonomi dan Bisnis, 2025)
Stock price volatility in the property and real estate sector reflects the industry's sensitivity to macroeconomic dynamics and policy shifts, making it a crucial concern for investors and corporate managers. This study aims to examine the effect of leverage and dividend policy on stock price volatility among property and real estate companies listed on the Indonesia Stock Exchange (IDX) during the 2023–2024 period. A quantitative approach was employed, utilizing secondary data obtained from annual financial reports of 77 purposively selected companies. The dependent variable stock price volatility was measured using the range between the highest and lowest stock prices. Leverage was measured by the Debt to Equity Ratio (DER), and dividend policy was represented by the Dividend Payout Ratio (DPR). Data were analyzed using multiple linear regression after passing classical assumption tests, including normality, multicollinearity, heteroskedasticity, and autocorrelation. The results show that neither leverage nor dividend policy has a significant effect on stock price volatility. These findings suggest that investors in this sector may prioritize external factors such as economic growth, interest rate fluctuations, and fiscal incentives over internal financial indicators when making investment decisions. The study implies that firms and policymakers should focus on strengthening macroeconomic fundamentals and sectoral stability to minimize market uncertainty and promote long-term investment confidence.